Early Detection for Malnutrition Risk Children with STRONG Kids: a Systematic Review - Riskika, Siti (D'Nursing and Health Journal (DNHJ), 2025)
The fulfilment of nutrition, especially in children, has a very crucial impact on their growth and development in the future, besides the fulfilment of good nutrition also supports the achievement of child health and can prevent diseases that can worsen the child's condition. Healthy children are the hope for the development of the country in the future, especially in achieving the Golden Indonesia 2045. This literature review aims to discuss the effectiveness of early detection of malnutrition risk in children using the STRONG Kids screening tool. The study was conducted using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses) analysis. The keywords used were early detection, children, malnutrition and STRONG Kids. Data was generated from 10 journals that have been obtained from a total of 106 journals obtained by the journal search method using the Sage Journal database and google scholar. The results showed that the STRONG Kids screening tool can provide an early picture in the early detection of suspected malnutrition risk in children aged 1 month to 18 years. STRONG Kids screening is effective and can be used as one of the screening tools in detecting children with suspected malnutrition risk.